Policymaking in education: Understanding influences on the Reading Excellence Act. - Edmondson, Jacqueline (Education Policy Analysis Archives, 2005)
Educators and researchers are being called to participate in language and literacy policy making (Roller & Long, 2001). In order to do so, however, there needs to be an understanding of how policy is made. Although policymaking often appears to be an irrational process, there are theories that exist to explain the influences and mechanisms that work to shape policies. In what follows, I adapt Theodoulou and Cahn's (1995) typology on policymaking in order to discuss how policy is made. These theories of policy making are explored within the context of the Reading Excellence Act to demonstrate how policymaking is read and explained. Given the limitations of these explanations, particularly the sense that there may be no explicit role for educators in such a process, an alternate theory of policymaking, critical pluralism, is proposed. This alternate typology suggests different roles for educators in relation to policymaking.